2019
DOI: 10.1177/1758573219841058
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid use is associated with lower transfusion rates in shoulder arthroplasty patients with preoperative anaemia

Abstract: Background: We evaluate tranexamic acid use in high-risk shoulder arthroplasty patients, hypothesizing that tranexamic acid will decrease transfusion rates in patients with low preoperative haematocrit. Methods: A retrospective review of shoulder arthroplasty patients with preoperative anaemia compared those treated with and without perioperative tranexamic acid. Inclusion criterion was any shoulder arthroplasty with a preoperative haematocrit (Hct) <38%. Tranexamic acid was given generally as 1 g intravenousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A recent retrospective study evaluated the efficacy of TXA in SA patients with preoperative anemia. 41 These authors found that the transfusion rate in this group of patients was 25% and TXA was associated with a reduction of 80% in transfusion rates. If the main aim with perioperative use of TXA is decreasing transfusions, it is possible that TXA in SA is a cost-effective intervention only in selected subgroups of patients.…”
Section: Discussionmentioning
confidence: 74%
“…A recent retrospective study evaluated the efficacy of TXA in SA patients with preoperative anemia. 41 These authors found that the transfusion rate in this group of patients was 25% and TXA was associated with a reduction of 80% in transfusion rates. If the main aim with perioperative use of TXA is decreasing transfusions, it is possible that TXA in SA is a cost-effective intervention only in selected subgroups of patients.…”
Section: Discussionmentioning
confidence: 74%
“…32,33 Our reported transfusion rate of 2.1% was lower than much of the reported TSA literature, which ranges from 3.9% to 25%. [34][35][36] This may owe to the increasing rates of successful tranexamic acid use in shoulder arthroplasty over the years, 37,38 as well as differing institutional protocols and potentially improved preoperative assessments.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 10 , 43 , 52 , 60 , 61 , 64 Several studies have reported using TXA in shoulder arthroplasty. 1 , 6 , 7 , 11 , 12 , 13 , 17 , 18 , 23 , 29 , 31 , 33 , 44 , 53 , 59 , 65 , 66 However, the existing studies have limitations, such as small sample size, low-quality studies, and different TXA administration.…”
mentioning
confidence: 99%